Plant-derived nodule-specific cysteine-rich peptides as potent antifungal agents against Cryptococcus neoformans: mechanisms of action, chimeric peptide enhancement, and immunomodulatory effects - Bettina Szerencsés; Csaba Papp; Alexandra Pál; Sándor Jenei; Nelli Németh; Csaba Vágvölgyi; Ferhan Ayaydin; Gabriella Endre; Éva Kondorosi; Ilona Pfeiffer (Current Research in Microbial Sciences)
The basidiomycetous yeast Cryptococcus neoformans is classified among the four critical fungal pathogens due to its capability of inducing life-threatening meningitis in immunocompromised individuals, particularly AIDS patients. The increasing prevalence of antifungal resistance and limitations of current treatments highlight the urgent need for novel therapeutic strategies. Antimicrobial peptides (AMPs), including plant-derived nodule-specific cysteine-rich (NCR) peptides, offer promising alternatives due to their broad-spectrum activity, multiple cellular targets, and minimal cytotoxic effects on mammalian cells. The aim of this study was to evaluate the anti-cryptococcal efficacy of NCR247, NCR335, NCR169C derivatives, and three synthetic chimeric peptides. Fifteen peptide derivatives and all three chimeras exhibited potent antifungal activity while demonstrating negligible cytotoxicity against murine macrophages. Among them, the X1-NCR247C chimera was the most effective, acting rapidly at low concentrations. Notably, its attachment to the yeast cells augmented the uptake of the cells by murine macrophages, suggesting that in addition to their direct fungicidal effects, antimicrobial peptides can intensify the immune response. These findings underscore the potential of NCR peptide derivatives as anti-cryptococcal agents and highlight the advantages of chimera peptides in improving therapeutic efficacy.